Avaliação da motivação dos estudantes do curso de medicina do centro Universitário Presidente Tancredo de Almeida Neves (UNIPTAN) em relação à estratégia aprendizagem em pequenos grupos - Jurgilas, Mirian Diená Pastorini (2022)
The main goal of this study is to analyze the motivation of 152 (72,4%) students, from the first to the fifth period, of the medical course of Universidade Presidente Tancredo de Almeida Neves (UNIPTAN), compared to the tutorial groups of ABP, which means Learning in small groups (ABP). The questionary Instructional Materials Motivation Survey, the valid version in Brazil (IMMS-BRV), was used to evaluate the motivation. 152 students participated in this study, mainly women (72,4%). The participants were in the first, second, third, fourth, and fifth periods of med school. The survey was applied on November of 2021 in Google forms. In the global motivation, it was noticed that the second period showed results significantly different from the other periods. Besides, the third-period students showed notably superior results in comparison to the other students. It wasn’t noticed considerably differences between the first, fourth, and fifth periods. The results represent the necessity of reviewing the curriculum, the problems, and the process of ABP facilitation in the second period.